Analysis of Policy Innovation in Traditional Market Revitalization from a Good Governance Perspective: A Case Study of Kolpajung Market in Pamekasan - Anam, Saiful; Habibi, Nur Syakherul; Syaiful, Syaiful (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2026)
This study analyzes the revitalization process of Kolpajung Market as a case of public policy innovation grounded in good governance principles. The revitalization incorporates three major innovations: digitalization of retribution and kiosk rental systems, financing through a Public–Private Partnership scheme, and commodity-based zoning arrangements. A descriptive qualitative approach was employed to explore policy dynamics, stakeholder participation, and challenges in implementing transparency, accountability, participation, and effectiveness. The findings reveal that although the revitalization reflects efforts toward structural transformation, the implementation of good governance principles remains partial. Public participation tends to be more procedural than substantive, while bureaucratic actors dominate decision-making processes. Information transparency is perceived as limited, and accountability mechanisms have not been systematically established. These issues hinder the policy’s effectiveness, as the improvement in the market’s socio-economic function after revitalization remains suboptimal. The theoretical reflection suggests that policy innovation has not yet led to an inclusive and sustainable governance transformation, as emphasized by Osborne and Gaebler and Habermas’s deliberative framework. This study underscores the importance of integrating policy innovation with institutional reform and the need for participatory communication strategies to strengthen society’s role as active agents in development. Strengthening local actor capacity, establishing community-based monitoring mechanisms, and developing result-based governance evaluation indicators are recommended for future traditional market revitalization initiatives.Keywords: Market Revitalization, Policy Innovation, Good Governance, Public Participation, Local Governance.